Task Conflict and Task Control: A Mini-Review - Littman, Ran; Keha, Eldad; Kalanthroff, Eyal (Frontiers in Psychology, 2019)
Stimulus-driven behaviors are triggered by the specific stimuli with which they are associated. For example, words elicit automatic reading behavior. When stimulus-driven behaviors are incongruent with one’s current goals, task conflict can emerge, requiring the activation of a task control mechanism. The Stroop task induces task conflict by asking participants to focus on color naming and ignore the automatic, stimulus-driven, irrelevant word reading task. Thus, task conflict manifests in Stroop incongruent as well as in congruent trials. Previous studies demonstrated that when task control fails, reaction times in congruent trials slow down, leading to a reversed facilitation effect. In the present mini-review, we review the literature on the manifestation of task conflict and the recruitment of task control in the Stroop task and present the physiological and behavioral signatures of task control and task conflict. We then suggest that the notion of task conflict is strongly related to the concept of stimulus-driven behaviors, and present examples for the manifestation of stimulus-driven task conflict in the Stroop task and additional tasks, including object-interference and affordances tasks. The reviewed literature supports the illustration of task conflict as a specific type of conflict which is different from other conflict types and may manifest in different tasks and under diverse modalities of response.